Implementation of Contextual Learning In Improving Early Children's Cognitive Ability - Novita Loka; Raden Rachmy Diana; Muhammad Sirril Wafa (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
ABSTRAK. Kemampuan kognitif anak usia dini saat ini menurun. Hal ini didukung berbagai faktor, salah satunya adalah kurangnya penggunaan pembelajaran yang inovatif yang mampu mengembangkan berbagai aspek perkembangan anak, khususnya ada kemampuan kognitif anak.. Pembelajaran yang bisa digunakan untuk meningkatkan kemampuan kognitif anak adalah pembelajaran kontekstual. Penelitian ini bertujuan untuk mengetahui kemampuan kognitif anak pada pembelajaran kontestual di Taman Kanak-kanak Islam Al-Ittifaqiah Indralaya. Penelitian ini berjenis kualitatif deskriptif dengan pengumpul data yakni observasi, wawancara dan dokumentasi dengan subjek penelitian anak usia 5-6 tahun di kelas B Maria al-Qibty Taman Kanak-kanak Islam al-Ittifaqiah Indralaya. Sedangkan analisa data yang digunakan dengan pendekatan Miles dan Huberman. Hasil penelitian menunjukkan bahwa kemampuan kognitif anak meningkat pada pembelajaran kontekstual ini. Hal ini dibuktikan dengan beberapa indikator kemampuan kognitif anak seperti meningkatnya kemampuan memecahkan masalah sederhana, memahami konsep sains dan konsep bilangan. Anak yang semula tidak mengetahui warna dan bentuk, ketika dilaksanakan pembelajaran kontekstual mulai memahami warna dan bentuk tersebut.Kata Kunci:  Pembelajaran Kontekstual, Kemampuan Kognitif, Anak Usia diniABSTRACTCognitive abilities in early childhood are currently declining. This is supported by various factors, one of which is the lack of use of innovative learning that can develop various aspects of children's development, especially children's cognitive abilities. Learning that can be used to improve children's cognitive abilities is contextual learning. This study aims to determine the cognitive abilities of children in contextual learning at Al-Ittifaqiah Islamic Kindergarten Indralaya. This research is a descriptive qualitative type with data collectors namely observation, interviews, and documentation with research subjects aged 5-6 years in class B Maria al-Qibty Islamic Kindergarten al-Ittifaqiah Indralaya. While the data analysis used the Miles and Huberman approach. The results showed that children's cognitive abilities increased in this contextual learning. This is evidenced by several indicators of children's cognitive abilities such as the increased ability to solve simple problems and understand science concepts and number concepts. Children who initially do not know colors and shapes, when contextual learning is carried out, begin to understand these colors and shapes.Keywords: Contextual Learning, Cognitive Ability, Early Childhood